High adult survival in a northern Eurasian Curlew (Numenius arquata) population - Pakanen, Veli-Matti; Kylmänen, Reijo (Ornis Fennica, 2023)
Wetland birds such as waders are in decline across Europe. Information on demography is vital for assessing the causes of population declines, but estimates are needed from multiple populations and time periods. We used capture-recapture data from 2013–2022 including 134 individuals to estimate sex-specific apparent adult survival of Eurasian Curlews from a population breeding on agricultural fields in Finland, a stronghold region for this species in Europe. Using the Cormack–Jolly–Seber-model that considers the recapture probability of individuals, we estimated apparent survival of adults to be 0.89 (SE 0.03) for males and 0.92 (SE 0.03) for females. Our estimates of adult survival are slightly higher than those previously estimated from Fennoscandian breeding grounds in 1980s–1990s (0.82–0.88). Thus, our results suggest that adult survival of populations breeding in northern Europe has not declined during the last decades. Our study supports the view that changes in reproductive success is the main cause of decline in the Eurasian Curlew populations.